Blended cement concrete - potential without misuse - Hussin, Mohd. Warid (2007)
There is now absolutely no doubt that the inclusion of siliceous admixtures as an essential component of concrete and as a partial replacement of Portland cement imparts significant enhancement of the basic characteristics of the resulting concrete, both in its fresh and hardened state. The use of pozzolanic materials in concrete is expected to raise, because, the incorporation of these materials such as pulverised fuel ash (PFA), silica fume and natural pozzolansin concrete contribute to the enhancement of quality of concrete in terms of its strength and durability.